Knowledge and Practice Regarding Household Waste Management among Middle Aged Adult People of Banepa Municipality - Lakhe, Dibyashwori; Manandhar, Sajita (Nepal Medical College Journal, 2022)
Globally, 2.6 billion people of the world population do not use proper method for waste disposal. Some 1.1 billion people still disposed of waste in the open places thus face many health related problems. According to the Central Bureau of Statistics, Currently, around 450 metric tons of solid waste is generated in Kathmandu every day. The objective of this study was to assess the Knowledge and Practice Regarding Household Waste Management Among Middle Aged Adult People in Banepa Municipality. A descriptive cross-sectional study was carried out among 60 adults using non-probability purposive sampling technique. Data was collected using pretested (r=0.85) face-to-face interview schedule with structured and semi structured Nepali version questionnaire. The collected data were analyzed in SPSS version 16th by using descriptive statistics such as frequency, percentage, mean, standard deviation, and inferential statics such as chi square test. The study shows, mean age of respondents was 48.36±4.747 years. The overall mean knowledge score was 39.5±9.62 which ranged from 19 to 58. The overall mean practice score was 17.41±2.1 which ranged from 13 to 20. The study was significant on the basis of training taken (p=0.016). The findings of this study showed that majority of the respondents had low level of knowledge but good level of practices. Therefore, based on the finding of the study, the household waste management can be improved by providing various awareness programs to the family members of the community so that various kind of disease can be prevented.